The Effect Of Papaverine On Mechanical Activity in Ileal Smooth Mascle Of Hedgehogs - Saied, F. N.; Gathwan, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This is the first time that the mechanical activity of Hedgehog i leal smooth muscle is a regular spontaneous contraction to be reported. It was found that the different concent1Â·ations of papaverine exerted different dcgces of inhibition on ileal smooth muscle. The minimum effective dose was (0.05) mM. Different concentration of acetylcholine and KCI caused tonic contraction in this kind of smooth muscle. High concentration of papaverine caused inst<mt relaxation in acetylcholine or Kcl- excited muscle. The inhibitory effect of the drug resul ted from the reduction of the available free calcium and caused relaxation.